MALDI-TOF Mass Spectrometry Is a Fast and Reliable Platform for Identification and Ecological Studies of Species from Family Rhizobiaceae - Ferreira, Laura; Sánchez-Juanes, Fernando; García-Fraile, Paula; Rivas, Raúl; Mateos, Pedro F.; Martínez-Molina, Eustoquio; González-Buitrago, José Manuel; Velázquez, Encarna (PLOS ONE, 2011)
Family Rhizobiaceae includes fast growing bacteria currently arranged into three genera, Rhizobium, Ensifer and Shinella, that contain pathogenic, symbiotic and saprophytic species. The identification of these species is not possible on the basis of physiological or biochemical traits and should be based on sequencing of several genes. Therefore alternative methods are necessary for rapid and reliable identification of members from family Rhizobiaceae. In this work we evaluated the suitability of Matrix-Assisted Laser Desorption Ionization-Time-of-Flight Mass Spectrometry (MALDI-TOF MS) for this purpose. Firstly, we evaluated the capability of this methodology to differentiate among species of family Rhizobiaceae including those closely related and then we extended the database of MALDI Biotyper 2.0 including the type strains of 56 species from genera Rhizobium, Ensifer and Shinella. Secondly, we evaluated the identification potential of this methodology by using several strains isolated from different sources previously identified on the basis of their rrs, recA and atpD gene sequences. The 100% of these strains were correctly identified showing that MALDI-TOF MS is an excellent tool for identification of fast growing rhizobia applicable to large populations of isolates in ecological and taxonomic studies.